Evaluation of the effect of learning on the full extent of inspiratory and expiratory pressure in healthy adults - Giuliani, Beatriz Branco (2016)
BACKGROUND: Measurements of maximal inspiratory and expiratory pressure are used to assess the pressure developed by the respiratory muscles and the passive elastic recoil of the pulmonary system. Such measurements are also used as criteria for weaning from mechanical ventilation, to determine the functional consequences of several systemic diseases and the development of lung diseases and neuromuscular disorders. The test in na outpatient setting is easy to perform, well tolerated and has predictive valueOBJECTIVE: To verify the presence of a learning effect in measurements of maximal inspiratory and expiratory pressures.METHODS: We performed 15 sequential measurements of Maximal Inspiratory Pressure and 15 of Maximal Expiratory Pressure in 71 individuals. Results for both series were compared throughout each series.RESULTS: The comparison between the first and the other measurements showed no statistically significant differences. (p > 0.05).CONCLUSIONS: There was no learning effect with 15 repeated measurements of Maximal Inspiratory or Expiratory Pressure in healthy adults.